Effect of aliphatic-based superplasticizer on rheological performance of cement paste plasticized by polycarboxylate superplasticizer. (10th February 2020) - Ma, Baoguo; Qi, Huahui; Tan, Hongbo; Su, Ying; Li, Xiangguo; Liu, Xiaohai; Li, Chunbao; Zhang, Ting
Highlights: Addition of AS in PCE system enhances bleeding and segregation resistance. Competitive adsorption between AS and PCE occurs. AS perturbs the adsorption ability of PCE. Abstract: Polycarboxylate superplasticizer (PCE) and aliphatic superplasticizer (AS) are widely used water-reducing agent in concrete. In actual practice, the addition of AS has been developed as a common way to alleviate the bleeding and segregation of concrete plasticized by PCE, while the main reason for this phenomenon is not clear. In this research, the effect of AS on dispersion of PCE was investigated. Adsorption behavior of AS and PCE and conformation of these polymers in liquid phase were analyzed with total organic carbon (TOC), conductivity, and dynamic light scattering (DLS). Finally, the experimental results were verified by molecular dynamics simulation, and the dispersion model was proposed to better understand the mechanism behind. The results showed that the effects of AS on the rheological performance of cement paste containing PCE was closely related to the added dosage, and it was observed that three stages were divided according to the dosage of AS. The main reason was due to competitive adsorption between AS and PCE. In addition, PCE molecules, which existed in the liquid phase due to competitive adsorption, would be crosslinked through calcium ions in pore solution, leading to the increase in plastic viscosity of cement paste despite with the decreased yield stress. These results explained why the addition of AS in PCE system could enhance the resistance to bleeding and segregation. These results would offer usefully experience for the application of multiple superplasticizer systems in practical engineering.